2023
DOI: 10.3390/cancers15041229
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Region of Cutaneous Melanoma Impacts Survival and Clinical Outcomes: A Population-Based Analysis

Abstract: Purpose: The objective was to determine the effects of the anatomic site of a cutaneous melanoma on the survival outcomes of diagnosed individuals. Methods: We conducted a cross-sectional study using data from the Surveillance, Epidemiology, and End Results Program (SEER) Database from 2004–2014 and included 178,892 cases of individuals diagnosed with cutaneous melanoma. Overall survival (OS) for each anatomic site as well as associated demographics, primary site, stage, and pathologic prognostic factors (Bres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Regarding the prognostic value of the demographic characteristics, there are conflicting reports. Similar to our findings, the male gender has previously been linked with decreased survival by some authors [ 3 , 24 ], while others found no such association [ 25 , 26 ]. Interestingly, an advanced age was only associated with a decreased OS but not PFS, which may be explained by the fact that older patients could have higher mortality rates due to other comorbidities that were not accounted for [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the prognostic value of the demographic characteristics, there are conflicting reports. Similar to our findings, the male gender has previously been linked with decreased survival by some authors [ 3 , 24 ], while others found no such association [ 25 , 26 ]. Interestingly, an advanced age was only associated with a decreased OS but not PFS, which may be explained by the fact that older patients could have higher mortality rates due to other comorbidities that were not accounted for [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Related to the gender distribution, the study emphasized the fact that the male gender predominates, with 58.1% of cases; this value being close to that obtained by an American trial based on a cohort of 178,000 cases from the period 2004-2014 where, in the case of melanomas located on the trunk, 66.1% were male patients [26]. Moreover, in our study, male gender was more frequent among subjects diagnosed with melanoma on the lower trunk than those with the upper location.…”
Section: Discussionsupporting
confidence: 81%
“…However, the H&N is a common location for BCCs 22 and melanomas 23 . Other studies with much larger cohorts from state or nation-wide cancer registries report up to 40% of BCCs 22 and approximately 20-30% of melanomas arising in the H&N 23,24 .…”
Section: Discussionmentioning
confidence: 98%